The Genomes of Four Meyerozyma caribbica Isolates and Novel Insights into the Meyerozyma guilliermondii Species Complex. Issue 3 (1st March 2018) - De Marco, Leone; Epis, Sara; Capone, Aida; Martin, Elena; Bozic, Jovana; Crotti, Elena; Ricci, Irene; Sassera, Davide
Abstract: Yeasts of the Meyerozyma guilliermondii species complex are widespread in nature and can be isolated from a variety of sources, from the environment to arthropods to hospital patients. To date, the species complex comprises the thoroughly studied and versatile M. guilliermondii, the hard to distinguish M. caribbica, and Candida carpophila . Here we report the whole genome sequencing and de novo assembly of four M. caribbica isolates, identified with the most recent molecular techniques, derived from four Diptera species. The four novel assemblies present reduced fragmentation and comparable metrics (genome size, gene content) to the available genomes belonging to the species complex. We performed a phylogenomic analysis comprising all known members of the species complex, to investigate evolutionary relationships within this clade. Our results show a compact phylogenetic structure for the complex and indicate the presence of a sizable core set of genes. Furthermore, M. caribbica, despite a broad literature on the difficulties of discerning it from M. guilliermondii, seems to be more closely related to C. carpophila . Finally, we believe that there is evidence for considering these four genomes to be the first published for the species M. caribbica . Raw reads and assembled contigs have been made public to further the study of these organisms.